The establishment and simulation of bidirectional Cockcroft-Walton circuit model. Issue 4 (6th November 2017) - Wu, Guozeng; Dong, Quanlin
Abstract : Purpose: The purpose of this paper is to improve the stability of high voltage DC power supply and reduce the ripple. Design/methodology/approach: The study was conducted using the simulation analysis model and numerical calculation. Findings: By increasing the output arm capacitance, the expression of ripple and times of the output arm capacitance and the auxiliary arm capacitance is derived. The output ripple is determined by the value of the output arm capacitance. Finally, the correctness of the method and the formula are verified using circuit simulation. Originality value: This paper presents a method to improve the power supply stability.